Immigrant-origin youth and the indecisiveness of choice for upper secondary education in Finland. (21st October 2017) - Kalalahti, Mira; Varjo, Janne; Jahnukainen, Markku
ABSTRACT: The educational transitions of Finnish youth of immigrant background are challenging. They confront more difficulties in a twofold manner: they have more difficulties in transitioning to upper secondary education and they seem to drop out of education more often than their Finnish-origin counterparts. This study aimed to accomplish a view of the complex intertwinement of attitudes and experiences with upper secondary education choices, gender and origin. We compared immigrant- origin students ( n = 161) with Finnish-origin students ( n = 156) in a survey conducted during the final year of comprehensive school. Our objectives were to analyse the variation in attitudes, experiences and aspirations concerning post-comprehensive transition in gender and origin of the youth, and to analyse the factors behind the indecisiveness of the transitions. We concluded that youth with immigrant origin in general, and boys in particular, share a contradiction we termed the 'paradox of immigrant schooling', which refers to the combination of a positivity toward education and difficulties in learning and studying. We also found an immigrant-related contradiction between determinant and quite high occupational aspirations, and uncertainty of upper secondary choices. Our outcomes indicate that the immigrant-origin youth confront the upper-secondary choices in a much more complex and multidimensional situation than their Finnish-origin counterparts.